2017
DOI: 10.1007/s10815-017-0884-8
|View full text |Cite|
|
Sign up to set email alerts
|

Attempts to improve human ovarian transplantation outcomes of needle-immersed vitrification and slow-freezing by host and graft treatments

Abstract: Ovarian sample preparation with slow-freezing + the improvement protocol appears to yield better implantation outcomes than needle-immersed vitrification with/without the improvement protocol. The real quality of frozen tissue can be assessed only after grafting and not after thawing/warming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…Hence, in this study the apoptosis of stroma cells was not investigated anymore. Interestingly, a recent study observed high rates of atretic follicles and apoptotic stromal cells after the use of NIV compared with after slow freezing plus the improvement protocol (host melatonin treatment and graft incubation with biological glue + vitamin E + vascular endothelial growth factor-A) [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, in this study the apoptosis of stroma cells was not investigated anymore. Interestingly, a recent study observed high rates of atretic follicles and apoptotic stromal cells after the use of NIV compared with after slow freezing plus the improvement protocol (host melatonin treatment and graft incubation with biological glue + vitamin E + vascular endothelial growth factor-A) [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant difference regarding apoptosis in stroma cells after VT was noted in this study. Moreover, the work finished by Abir et al [40] mainly focused on the comparison of different protocols rather than VT devices. Additionally, the diameter of the acupuncture needle used in our NIV study was 0.18 mm, while the insulin needle with a diameter of 0.25 mm was used in Abir's study [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated that MLT, as a highly lipophilic molecule, can easily cross the cell membranes and show antioxidant and anti-apoptotic effects ( Kleszczyński et al, 2016 ; Reiter et al, 2016 ; Zhang et al, 2019 ; Tamura et al, 2020 ). Moreover, some recent studies have reported the beneficial effects of MLT on improving the preservation of OTs and auto-transplantation ( Abir et al, 2017 ; Goodarzi et al, 2017 ; Gül et al, 2018 ). Nevertheless, the specific mechanisms of MLT underlying its protective role in stress-induced oxidative damage of follicles are less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the valuable data obtained in different animal models by researchers in developmental biology and veterinary field have to be considered inspirational for the work in humans. In the last two decades, several groups could prove that early preantral/secondary follicles can be grown up to a stage where the oocyte can re-initiate meiosis, although still at a low final yield, in isolated follicle culture systems in mice (Cortvrindt & Smitz 2001, Xu et al 2006, 2009a, Hornick et al 2013, large domestic animals (Songsasen et al 2011, Silva et al 2015, non-human primates (Xu et al 2009b(Xu et al , 2010(Xu et al , 2011a(Xu et al ,b, 2013(Xu et al , 2017 and in human (Telfer et al 2008, Xu et al 2009a, Laronda et al 2014, Xiao et al 2015, Yin et al 2016, Abir et al 2017. More sophisticated in vitro systems are being designed using the most recent knowledge from the omics, bio-printing technologies and microfluidics.…”
Section: Introductionmentioning
confidence: 99%